PENGEMBANGAN METODE PRODUKSI TEH UNTUK PENINGKATAN PENDAPATAN PETANI GAMBIR DI DURIAN TINGGI KABUPATEN LIMA PULUH KOTA - Muhammad Fadli; Agriqisthi Agriqisthi; Luthfil Hadi Anshari (Jurnal Hilirisasi IPTEKS, 2021)
Gambir (Uncaria gambir Roxb.) is the only specific commodity from West Sumatra, especially in the District of Fifty Cities. The world's largest producer of gambier is in West Sumatra. Parts that have economic value from gambier plants are catechins. Catechins are secondary metabolites of the gambier plant, which plants use to protect themselves from biotic and abiotic disturbances. This compound also has properties as a beverage refresher apart from its healing ability. This activity aims to help minimize the obstacles faced by the Nine Farmers Group. This activity was carried out at the Nine Farmers Group in Durian Tinggi, Kapur IX District, Lima Puluh Kota Regency, West Sumatra. Producing refreshments from the gambier plant is done by developing a straightforward method. The simple steps that require further development of this production technology consist of picking gambier leaves, drying, milling, and packaging. Constraints that limit production are product standardization and packaging design. The ongoing tea production by the Nine Farmers Group has dramatically helped increase the income of gambier farmers. Increasing the income of gambier farmers in Kapur IX can be done using a simple technological approach to producing gambier tea. The gambier tea produced by the Nine Farmers Group allows gambier farmers to earn income apart from the fluctuating price of gambier tea production. Gambier tea which the Nine Farmers Group has successfully produced needs to be standardized and product packaging design to expand the market.